2019
DOI: 10.13005/bpj/1638
|View full text |Cite
|
Sign up to set email alerts
|

Responses of the Human Body to the Effect from Exposure to Anthropogenic Increase of Ambient Air Pollution

Abstract: In modern urbanized conditions, the human population is experiencing a constant effect of various exogenous factors - social, economic, environmental. That is quite a challenge to determine the leading or dominant influence factor of the current total. At the same time, there is no doubt that environmental impacts on the human population adversely affect the population health. Human habitation in highly polluted ambient air leads to the diseases of respiratory, nervous and circulatory system, and may contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…It is projected that for 2030 landfills will emit 959 Mg CO 2 eq −1 ( EPA, 2013 ). The presence of landfill sites has also been correlated with the increase of respiratory, circulatory and nervous system disorders in the surrounding population ( Latushkina et al, 2019 ). One study carried out by Rabl et al (2008) found that the external cost of landfilling (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…It is projected that for 2030 landfills will emit 959 Mg CO 2 eq −1 ( EPA, 2013 ). The presence of landfill sites has also been correlated with the increase of respiratory, circulatory and nervous system disorders in the surrounding population ( Latushkina et al, 2019 ). One study carried out by Rabl et al (2008) found that the external cost of landfilling (i.e.…”
Section: Introductionmentioning
confidence: 99%